AI as a Resource for Second Language Socialisation in Doctoral Thesis Writing: A Comparative Study of New Zealand and Malaysia - Bakar, Farhana; Mazzocco, Patrick (Semarak International Journal of Current Research in Language and Human Studies, 2025)
The rapid advancement of generative artificial intelligence (AI) has reshaped academic writing practices in higher education, yet its role in the socialisation of second language (L2) doctoral students is still evolving. This study addresses how L2 doctoral students in two distinct contexts, New Zealand (an English dominant environment) and Malaysia (an English as a Second Language context), use AI tools in their thesis writing, and how these tools mediate their socialisation into academic discourse communities. Data were collected from two focus group interviews, one from New Zealand and one from Malaysia, with international doctoral students and analysed thematically through the lens of second language socialisation. Findings reveal that AI supports students at three levels: 1) linguistically, by providing grammar correction, vocabulary enhancement, and translation; 2) rhetorically, by scaffolding argument structures, theoretical frameworks, and literature synthesis; and 3) affectively, by boosting confidence while also eliciting hesitation such as guilt and dependency. The comparative analysis highlights contextual differences, with New Zealand L2 doctoral students emphasising linguistic refinement and identity negotiation, and Malaysian L2 doctoral students drawing on AI more for critical analysis and emotional reliance. These insights extend second language socialisation theory by conceptualising AI as a mediating resource in doctoral writing socialisation and point to urgent implications for supervisory practice, institutional policy, and ethical AI integration in postgraduate education.